1972, Reggio Emilia and the school books - Nicola Zuccherini (Italiano a scuola, 2023)
Fifty years have passed since both Gianni Rodari's “Meetings on the Fantastic”, from which Grammatica della fantasia originated, and I pampini bugiardi by Marisa Bonazzi and Umberto Eco were published. The paper is inspired by this double anniversary and aims to reflect on the enduring relevance of these texts and those experiences, with an invitation to reconsider their scientific and cultural foundations. In particular, reference is made to "other tools of analysis and measurement" that Rodari identified in scientific linguistics, semiotics and anthropology and which, to this day, remain largely extraneous to the culture of teaching practices and textbooks.